Competing values framework and its impact on the intellectual capital dimensions: evidence from different Portuguese organizational sectors - Ferreira, A. (Knowledge Management Research and Practice, 2014)
Organizational culture and intellectual capital (IC) have been important topics in the current organizational literature. However, few studies have analysed the correlations between these constructs. From this evidence, the main goal of the present study is to examine the correlation between the perceptions of organizational culture and the perception of IC measures. A sample consisting of 401 workers from the technological, health and services sector responded to the Organizational Culture Assessment Instrument and the Intellectual Capital Scale. Results show that the Competing Values Framework dimensions (clan, adhocracy, hierarchy and market cultures) are correlated with the three IC dimensions studied (customer, structural and human capital). Our results also show that the culture explained variance varies across organizational sectors. The current study provides an initial contribution to the investigation of the correlation between perceived organizational culture and IC measures. The discussion and analysis ends with an integrated framework with practical implications for management, followed by suggestions and guidelines for future studies.